Biological versus mechanical heart valve prosthesis during pregnancy in women with congenital heart disease. (1st October 2018) - Lameijer, Heleen; van Slooten, Ymkje J.; Jongbloed, Monique R.M.; Oudijk, Martijn A.; Kampman, Marlies A.M.; van Dijk, Arie P.; Post, Marco C.; Mulder, Barbara J.; Sollie, Krystyna M.; van Veldhuisen, Dirk J.; Ebels, Tjark; van Melle, Joost P.; et al.
Abstract: Background: We evaluate pregnancy outcome and anticoagulation regimes in women with mechanical and biological prosthetic heart valves (PHV) for congenital heart disease. Methods: Retrospective multicenter cohort studying pregnancy outcomes in an existing cohort of patients with PHV. Results: 52 women had 102 pregnancies of which 78 pregnancies (46 women) ≥20 weeks duration (59 biological, 19 mechanical PHV). Miscarriages ( n = 19, ≤20 weeks) occurred more frequently in women using anticoagulation ( P < .05). During 42% of pregnancies of women with mechanical PHV a combined low molecular weight heparin (LMWH) vitamin-K-antagonist anticoagulation regime was used ( n = 8). Overall, cardiovascular, obstetric and fetal/neonatal complications occurred in 17% ( n = 13), 68% ( n = 42) and 42% ( n = 27) of the pregnancies. Women with mechanical PHV had significantly higher cardiovascular (12% vs 32%, P < .05), obstetric (59% vs 85%, P = .02) and fetal/neonatal (34% vs 61%, P < .05) complication rates than women with biological PHV. This was related to PHV thrombosis ( n = 3, P < .02), post-partum hemorrhage ( P < .02), cesarean section ( P < .02), low birth weight and small for gestational age (both P < .05). PHV thrombosis occurred in 3 pregnancies, including 2/5 pregnancies with pulmonary mechanical PHV. PHV thrombosis was related to necessary cessation of anticoagulation therapy or insufficient monitoring of LMWH. Other cardiovascular complications occurred equally frequent in both groups. Conclusion: Complications occur more often in pregnancies of women with a mechanical PHV than in women with a biological PHV, mainly caused by PHV thrombosis and bleeding complications. Meticulous monitoring of anticoagulation in pregnant women is necessary. Women with a pulmonary mechanical PHV are at high risk of complications. Highlights: Women with mechanical PHV have higher pregnancy complication rates. This is due to (possibly avoidable) PHV thrombosis and post-partum hemorrhage. Women with pulmonary mechanical PHV are at high risk of complications. The choice for a biological PHV in these young women is not indisputable.